Phytotherapy in Diabetic Foot Ulcers: A Promising Strategy for Effective Wound Healing. Issue 3 (3rd April 2023) - Miraj, Sonal Sekhar; Kurian, Shilia Jacob; Rodrigues, Gabriel Sunil; Saravu, Kavitha; Rao, Mahadev; Raychaudhuri, Siba Prasad; Downs, Bernard W.; Bagchi, Debasis
Abstract: Despite the advancement in wound care, the effective therapy of chronic diabetic ulcers continues to be a challenge. Wound healing is a highly controlled process, which involves a sequence of complex overlapping steps. This healing pathway comprises of hemostasis, inflammation, proliferative, and remodeling phases. Recent evidence suggests that phytomedicines can prevent or repair different kinds of destructive cellular damage, including chronic wounds. Several phytochemicals such as polyphenols, alkaloids, flavonoids, terpenoids, and glycosides have pleiotropic effects, including stimulation of fibroblast proliferation, the main step in wound healing. Besides, the mechanism involves induction of collagen synthesis, migration, and reepithelization and their antimicrobial, antioxidant, anti-inflammatory, and immunomodulatory actions. Similarly, the use of phytochemicals alone or as an adjuvant with standard therapy has demonstrated promising results in managing complications in the diabetic foot. For instance, the extract of Carica papaya has been shown antioxidant, antimicrobial, and anti-inflammatory, and immunomodulatory effects, which, together with proteolytic enzymatic activity, contributes to its wound healing property. It is generally believed that phytotherapy has no or minimal toxicity than synthetic therapeutic agents, favoring its use in diabetic foot ulcer management. The current review highlights the selected phytochemicals and their sources; and potential application in diabetic foot ulcer management. Key teaching points and nutritional relevance: Currently, phytochemicals have been shown wide potential in disease. management including alleviating clinical manifestations, preventing degenerative disease, and curing illness. Increased evidence of phytochemical as anti-infective and anti-inflammatory suggests its role in the management of diabetic foot ulcer(DFU). Potential benefit along with minimal adverse effect favors its application as adjuvant therapy. Further research is needed to standardize its dose and formulation to enhance its clinical application in DFU management.